Survey of ICT and Education in Africa : Senegal Country Report - Fall, Babacar (World Bank, Washington, DC, 2012)
This short country report, a result of larger Information for Development Program (infoDev) - supported survey of the Information and Communication Technologies (ICT) in education in Africa, provides a general overview of current activities and issues related to ICT use in education in the country. Senegal's hand on commitment to incorporating ICT in education is still in the beginning stages of progress and evaluation. Although Senegal's public officials and government bodies recognize ICT as a powerful engine for progress in economic expansion and modernization and have a national ICT policy in place, it has not yet been integrated into the education sector in any kind of formal policy. However, the Ministry of Education and several organizations have taken initiatives to launch and continue activities that will facilitate the modernization of schools and other educational institutions. Initiatives have also been made in the informal sector, such as the United Nations Educational, Scientific, and Cultural Organization (UNESCO) Community Multimedia Center Scale-Up Project, to make ICT accessible to community members. Although obstacles remain, such as the need for more telecommunications infrastructure and computer materials, the outlook for integrating ICT into Senegal's education system is very optimistic.